EFFECTS OF SUGARCANE STRAW ON GRASS WEEDS EMERGENCE UNDER FIELD CONDITIONS - Silva Junior, Antonio Carlos da [UNESP]; Martins, Cibele Chalita [UNESP]; Martins, Dagoberto [UNESP] (Univ Federal Uberlandia, 2016)
This study aimed to assess the effects of sugarcane straw soil cover on Brachiaria plantaginea, Panicum maximum and Digitaria nuda seedlings emergence. The experiment was carried out in a soil classified as Red Nitosol. Seven different amounts of sugarcane straw soil cover were assessed (0, 3, 6, 9, 12, 15 and 18 ha(-1)). SP83-2847 variety straw was used. The experiment was arranged in a randomized blocks design, with four replications. Each experimental unit contained three species, which were allocated in the center of each plot, sown at 1 cm depth in a demarcated area. Different amounts of straw were distributed in this area. The sowing rate was used in order to obtain 1200 plant m(-2). Two phases comprised the study. In the first phase, weeds emerged in sugarcane straw cover soil were assessed at 9, 12, 19, 34 and 43 days after sowing (DAS) and the second phase assessed plant emergence after straw removal, at 89, 130, 175, 196, 217 and 234 DAS. Seedlings that had over 1 cm shoot and were visible in all assessments were considered emerged. Soil cover sugarcane straw amount influenced the different species germination dynamics. In the first phase, species differential response was observed regarding used straw amount. In the second phase, after straw removal, there was higher germination for B. plantaginea and D. nuda, while P. maximum showed lower emergency, regardless of the used straw amount.
Keywords: Panicum maximum; Brachiaria plantaginea; Digitaria nuda; Unburned sugarcane; Seed bank